Dual invariant Lagrange formulation of electrodynamics - Strazhev, Vasilij I. (Journal of the Belarusian State University. Physics, 2019)
The dual invariant Lagrange formulation of electrodynamics is based on the Cabibbo – Ferrari introduction of two potentials to the description of electromagnetic field without increase of its degrees of freedom. It is realized through invariance requirement of field tensor under specialized gauge transformations of potentials. The used Lagrangian is dual invariant, simultaneously it is invariant of specialized gauge transformations defined on solutions of Maxwell equations. The same procedure of consideration is realized in the case of dual symmetrical formulation of electrodynamics with electrically charged particles.
Keywords: dual symmetry; Cabibbo – Ferrari two potential description; Lagrangian of electromagnetic field